The role of ideology in creating new nations in the USSR and strengthening a centralised state-The example of the Dungans in central Asia - Kokaisl, Petr; Hejzlarová, Tereza (Heliyon, 2023)
This paper describes the role of the totalitarian state in changing ethnic identity. To solve the question of nationality, the Soviet Union drew upon the ideologies of ultra-radical theorists of the 19th century, whose goal was to change society by removing several major institutions - for example, through the liquidation of family or private property, in addition to creating a national group. Numerous paradoxes emerged when putting these initial theories into practice because they were full of internal contradictions. The example of the Dungans shows how the state created a new ethnic group, which it supported in every possible way, and then, in the next phase, it clearly persecuted this ethnic group. In the implementation of state interventions, it is clear that the main declared elements of ethnic identity are extremely volatile and their meaning varies considerably. Whereas earlier Soviet ideology sought to present the Dungans as a group vastly different from its ancestors in China, contemporary Chinese ideology emphasises the similarities between the two groups.
Keywords: Central Asia; Ideology; China; Ethnic minorities; Creating new nations; Ethnic identity; USSR; Totalitarian state